Manipulating the directional emission of monolayer semiconductors by dielectric nanoantenna arrays. (4th January 2022) - Liu, Pengbo; Zhang, Zhenghe; Lang, Man; Lu, Wanli; Bai, Ping; Chen, Zefeng; Wang, Shaojun; Li, Xiaofeng
Abstract: Collective Mie resonances in silicon (Si) nanoparticle arrays (NPAs) feature low absorption losses and strong field enhancement extending to a large area. They provide a high-efficient scheme to manipulate the emission properties of monolayer semiconductors. However, the poor quality factor of the current reported Si NPA limits the performance of light-emitting devices. It is mainly due to the constituent materials of nanoparticles being amorphous or polycrystalline Si, which have higher absorption coefficients in comparison with monocrystalline silicon (c-Si) among the visible band. This invited paper demonstrates a versatile technique to integrate the atomic layers onto the c-Si NPA. We show that our method can fully preserve the monolayer sample. We further investigate the directional emission tailored by the NPA with different diameters by combining back-focal-plane imaging and reciprocity simulations. The flexible tune of the geometry parameters of NPAs can offer many possibilities to control and manipulate the emission from monolayer semiconductors by engineering their photonic environments.